Exploring the genomic basis of early childhood caries: a pilot study. Issue 2 (23rd October 2017) - Ballantine, Jami L.; Carlson, Jenna C.; Ferreira Zandoná, Andrea G.; Agler, Cary; Zeldin, Leslie P.; Rozier, Richard Gary; Roberts, Michael W.; Basta, Patricia V.; Luo, Jason; Antonio‐Obese, Mikafui E.; McNeil, Daniel W.; Weyant, Robert J.; et al.
Abstract : Objective: A genetic component in early childhood caries (ECC) is theorized, but no genome‐wide investigations of ECC have been conducted. This pilot study is part of a long‐term research program aimed to: (1) determine the proportion of ECC variance attributable to the human genome and (2) identify ECC‐associated genetic loci. Methods: The study's community‐based sample comprised 212 children (mean age=39 months; range = 30–52 months; males = 55%; Hispanic/Latino = 35%, African‐American = 32%; American Academy of Pediatric Dentistry definition of ECC prevalence = 38%). Approximately 2.4 million single nucleotide polymorphisms (SNPs) were genotyped using DNA purified from saliva. A P < 5 × 10 −8 criterion was used for genome‐wide significance. SNPs with P < 5 × 10 −5 were followed‐up in three independent cohorts of 921 preschool‐age children with similar ECC prevalence. Results: SNPs with minor allele frequency ≥5% explained 52% (standard error = 54%) of ECC variance (one‐sided P = 0.03). Unsurprisingly, given the pilot's small sample size, no genome‐wide significant associations were found. An intergenic locus on 4q32 (rs4690994) displayed the strongest association with ECC [ P = 2.3 × 10 −6 ; odds ratio (OR) = 3.5; 95% confidence interval (CI) = 2.1–5.9]. Thirteen loci with suggestive associations were followed‐up – none showed evidence of association in the replication samples. Conclusion: This study's findings support a heritable component of ECC and demonstrate the feasibility of conducting genomics studies among preschool‐age children.